2021
DOI: 10.3390/jcm10215137
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Psychological Distress during the First Stage of the COVID-19 Pandemic on the Chilean Population

Abstract: The health effects of COVID-19 continue to raise doubts today. In some areas, such as mental health, these doubts have scarcely been addressed. The present study analyses the effects on psychological distress during the first phase of the pandemic in Chile. A cross-sectional descriptive study was performed by using a questionnaire validated in Spain and adapted for Chile. Between 22 April and 16 December 2020, 3227 questionnaires were collected from the 16 regions of Chile, using non-probabilistic snowball sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
(70 reference statements)
3
10
0
Order By: Relevance
“…Although we also confirmed+ the existence of psychological distress in the studied setting, its level (GHQ ≥ 3 = 62.6%) is not very different from that observed in other countries where the same instrument was used, such as Argentina (60.9%) [13], Spain (65.2%) [35], Peru (59.68%) [11], and Portugal (57.2%) [36], and it was lower than in Chile (78.83%) [12]. This study also found a perceived need for psychological support in professionals and volunteers involved in responding to the pandemic, including those affected by the disease and their families, a fact that has been previously reported in health care workers [37] and non-health care workers [28].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Although we also confirmed+ the existence of psychological distress in the studied setting, its level (GHQ ≥ 3 = 62.6%) is not very different from that observed in other countries where the same instrument was used, such as Argentina (60.9%) [13], Spain (65.2%) [35], Peru (59.68%) [11], and Portugal (57.2%) [36], and it was lower than in Chile (78.83%) [12]. This study also found a perceived need for psychological support in professionals and volunteers involved in responding to the pandemic, including those affected by the disease and their families, a fact that has been previously reported in health care workers [37] and non-health care workers [28].…”
Section: Discussionsupporting
confidence: 80%
“…These statistics placed the country among those with the highest number of cases and deaths per capita in the world [ 4 , 5 ]. Many studies have assessed the influence of the COVID-19 pandemic on the development of psychological distress in the general population and health care workers of Ecuador, evidencing a moderate-high level of psychological distress in both groups [ 6 , 7 , 8 , 9 , 10 ], in agreement with other studies in nearby Latin American countries [ 11 , 12 , 13 , 14 ].…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Some people who have potentially been exposed to a SARS-CoV-2 virus were in quarantine in order to reduce the risk of infecting others. Although social distancing restricts movement less than a quarantine, in both cases, the same psychological effects occurred, such as anxiety, depression, post-traumatic stress, frustration, confusion, and anger [ 3 , 4 , 5 , 6 ]. In the group of young adults (18–23 years of age), females were at more risk for increased loneliness and depression compared to males [ 7 ].…”
Section: Introductionmentioning
confidence: 99%